Acinar cystic transformation of the pancreas causing progressive main pancreatic duct dilation: a diagnostic dilemma. Issue 3 (28th March 2023) - Sebastian, Elizabeth; Longano, Anthony; Wei, Matthew Y K; Goonawardena, Janindu; Bull, Nicholas; Hassen, Sayed
ABSTRACT: Acinar cystic transformation (ACT) of the pancreas is a rare benign lesion. We describe a case of ACT with progressive main pancreatic duct dilation concerning for malignancy, not previously described. We discuss the difficulties associated with imaging and biopsy in differentiating this pathology from other cystic lesions, including intraductal mucinous papillary neoplasms.